God's unruly friends : dervish groups in the Islamic later middle period, 1200-1550 - Karamustafa, Ahmet T., 1956- (University of Utah Press, 1994)
"Wandering dervishes formed a prominent feature of most Muslim communities well into the modern period, surviving in some regions even today. Shocking in appearance, behavior, and speech, these social misfits were revered by the public, yet denounced by cultural elites. God's Unruly Friends is the first in-depth and comprehensive survey of this enigmatic type of piety, tracing the history of the different dervish groups that roamed the lands in Western, Central and South Asia, as well as the Middle East and Southeast Europe."